'Happy and excited': Perceptions of using digital technology and social media by young people who use augmentative and alternative communication. (June 2014) - Hynan, Amanda; Murray, Janice; Goldbart, Juliet
Young people are using digital technology and online social media within their everyday lives to enrich their social relationships. The UK government believes that using digital technology can improve social inclusion. One well-recognized outcome measure for establishing social inclusion is to examine opportunities for self-determination. Individuals with physical disabilities and complex communication needs who use forms of augmentative and alternative communication (AAC) have lower social participation opportunities. The integration of mainstream digital technology into high-tech forms of AAC (voice output communication aids), and the recent appearance of voice output applications, or 'apps', on Apple and Android products, has provided increased opportunities for people who use AAC to engage with digital technology. Research exploring this area, especially in regard to online social media, with people who use AAC is extremely limited, and a specific gap for self-reported experiences exists within the UK. This article describes qualitative, interview-based, grounded theory research with 25 adolescents and young adults who use AAC about their use of digital technology and online social media. The data presented here are part of a larger study, and the findings within this article suggest that participants have a desire to use the internet and online social media as it is perceived to increase opportunities for self-determination and self-representation whilst enriching friendships. The wide diversity of literacy and language skills amongst participants, as well as accessibility challenges, mean collaborating with others and receiving technical support from educational settings, families and friends are vital.